SOCIAL MEDIA AND COMMUNITY IN PANDEMIC COVID-19 - Vinta Sevilla (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
The rapid flow of information about Covid-19 made people focus their attention on social media. This situation has made social media no longer a place to share about daily activities, but information about Covid-19. Finally, social media users become producers, distributors, and consumers of information about Covid-19 that is on social media. This paper discusses the use of social media that used as a means of information by the public, and various aspects relating to the information habits of the community during the Covid-19 Pandemic.Keywords: Social media, information, covid-19 pandemic